Increasing Community Creativity Through Ecoprint Training In Dempelrejo Village - M. Nursutan Indra Mukti; Laeli Nur Fajriah; Syifa Suci Meilani; Mila Mustahiqotus Syar’iyah; Ahmad Ulil Albab; Ulfatu Asyifah; Zulfatul Karimah; Devanty Kamila Maulidiya; Saifudin Saifudin (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2024)
Nowadays, people's use of plastic bags is increasing, especially in the domestic environment. Even though plastic waste is an item that is difficult to decompose naturally. This service seeks to understand the problems that exist in society in the form of the large amount of plastic waste. This service is part of community service. Namely in the form of ecoprint training whose products can be a substitute for plastic bags in everyday life. Service activities take the form of ecoprint training using community education and observation methods. The subject of this service is women in Dempelrejo Village. This activity uses tote bags and leaves around the house as the main materials. The stages of this service activity include: 1. Initial planning and assessment, starting from identifying and observing the conditions of the Dempelrejo community to determining the advantages and disadvantages as well as the objectives of the ecoprint training. 2. Preparation stage, providing equipment, materials and implementation location. 3. Implementation stage, explaining the techniques on how to have leaves, hitting the leaves, and soaking the totebag. The aim of the ecoprint training activity is to provide education to the Dempelrejo community to reduce the community's tendency to replace plastic bags with environmentally friendly tote bags. Apart from that, ecoprint products can be used many times to meet household needs. Moreover, the materials used in making ecoprints are materials that are easily accessible. This dedication emphasizes the importance of loving and protecting nature from the dangers of plastic waste which threatens the environment.